Gambaran MRI Jantung pada Kasus ARVC dengan Menggunakan Sequence T1 Darkblood Axial dan T1 Spir Axial - Sriyatun Sriyatun; Gandon Sari; Ari Sasongko; Rofi Fatmawati (Jurnal Kesehatan Manarang, 2019)
Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) is a cause of sudden cardiac death in otherwise healthy young adult including healthy adults, even young age. ARVC is an inherited cardiomyopathy characterized by life-threatening ventricular arrhythmias and slowly progressive ventricular dysfunction. To diagnose ARVC is indicated by the ARVC facts that are common are marked by heart palpitations, fatigue, lack of awareness, and chest pain. ARCV often occurs in patients with indications of diabetes, hypertension, hyperlipidemia, and also chronic kidney disease. Task Force of ARVC criteria in 1994 and then revised in 2010 set by the WHO/ISFC. To identify clinical characterictics of ARVC using CMR. The design of this study was qualitative descriptive, which was done by observational method using MRI 1.5 Tesla. The subject was an adult patient who did Cardiac MRI examination in National Cardiovascular Centre Harapan Kita on March 2018. The collected data were diagnostic images of CMR sequence. Then, it compared with diagnostic criteria of ARVC which was indicated by Task Force. The result of this study of several ARVC diagnostic criterias in Cardiac MRI examination with T1 Black Blood sequence is clear and accurate in indicating the presence of fat infiltration, CINE sequence is clear in visualizing the dilatation in the right ventricle, wall motion abnormalities, accordion sign, bulging, and LGE clearly shows fibrosis. The detection of right ventricular enlargement, fatty infiltration, fibrosis, and wall motion abnormalities in CMR is useful in the diagnosis of ARVC.